The role of modern office administrative services in supporting public services in Bekasi Regency - Udaya Madjid; Ahmad Averus Toana; Muh. Ilham; Dahyar Daraba (Program Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to analyze the description of modern office administrative services in supporting public services. The research method used is descriptive qualitative, employing surveys to collect data from respondents who are members of the public who have interacted with office administrative personnel. The research results indicate that administrative personnel have a positive response to every member of the public seeking services, and they provide problem-solving solutions to visiting individuals, demonstrating a satisfactory level of satisfaction, although it is considered less important by the public. However, the services provided do not meet expectations. Therefore, there is a need for improvement in the availability of integrated information systems that connect internal units with external stakeholders and the provision of services based on Standard Operating Procedures (SOP) to satisfy the public. The services provided offer a satisfactory level of satisfaction but need to be maintained to avoid excess.